THE CONCEPT OF ISMAIL RADJI AL-FARUQI ISLAMIC EDUCATION AS A SOLUTION IN THE MILLENNIAL ERA - Halimatus Sa'diyah (Journal of Contemporary Islamic Education, 2021)
Of several problems in the Millennial era, one of them is the westernization of science, including Islamic education. So it is necessary to find a solution by Islamizing science as conceptualized by Ismail Radji al-Faruqi. This research is a library research using qualitative descriptive analysis. Data was collected from various kinds of reading sources in the form of scientific articles and books and other supporting references, then ancarried content analysis was in-depthout to find solutions to educational problems in the millennial era. The results of the research show that the concept of Islamic education Ismail Radji al-Faruqi is a leading Muslim intellectual who has responded positively to the development of science and technology, but he still puts the principle of tauhid in his idea of ​​Islamization of science. Through a work plan arranged systematically with five objectives and twelve stages al-Faruqi was able to realize his program. It is important to review the concept of education to be re-realized in the current millennial era.